Optimization of Close-In Phase Noise for Microwaves Generated With Kerr Combs Using Brillouin-Assisted Pump Depletion - Khaldoun Saleh; Yanne K. Chembo (IEEE Photonics Journal)
We report a method to improve the close-in phase noise performance of microwave signals generated using Kerr optical frequency combs. We propose a technique based on Brillouin-assisted pump depletion, and we show that the resulting phase noise close to the microwave carrier can be significantly lowered. We consider microwaves with 18 and 30 GHz frequency and achieve phase noise improvements up to 10 dB for close-in phase noise (offset $<10$ kHz). This technique targets applications where particularly high spectral purity is required at sub-kHz offset from the carrier frequency.